A diurnal new species of Stigmatodon (Bromeliaceae, Tillandsioideae) from vertical rock walls of the Atlantic Forest inselbergs, Espírito Santo state, Brazil - Couto, Dayvid R.; Manhães, Vitor Da Cunha; Leme, Elton M. C. (Phytotaxa, 2025)
The authors describe and illustrate Stigmatodon minimus, a new species with the smallest stature within the genus, and discuss its taxonomic affinities and conservation status. Furthermore, this new species is the only one, among all others with typical tubo-laciniate stigma type, to present diurnal anthesis, reddish-wine to purplish-wine bracts, and unappendaged white petals, contrasting with the morphological characteristics of other previously known species of Stigmatodon s.str. The new species is closely to S. amadoi, with which it is compared, and considered a microendemic, Vulnerable [VU: D2] species due to its restricted habitat, reduced population size, and threats from ornamental rock mining.